(untitled) (New York, NY, 2004)
This encyclopedia is a comprehensive reference work for the field of special education subsequent to the passage of education for all handicapped children Act of 1974. This 2nd edition offers a desk reference for special educaters, school psychologists educational and clinical psychologist educational diagnosticans, resource and related teachers and the parents of children receiving or in need of special education services. Articles on this topics also were collected in this work
Keywords: Special education,Children with disabilities,People with disabilities; Education,Education; United States,United States,United States